2019
DOI: 10.9734/afsj/2019/v11i430066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watermelon Rind (Citrullus lanatus) Addition on the Chemical and Sensory Quality of Sorghum Based Mumu

Abstract: Aims: The aim was to evaluate the effect of watermelon rind addition on chemical and sensory properties of sorghum based mumu. Study Design: The experimental design used was the complete randomized design (CRD) and the Data obtained was subjected to Analysis of Variance (ANOVA) followed by Tukey’s Least Significant Difference(LSD) test to compare treatment means; differences was considered significant at 95% (P≤0.05) (SPSS Version 21 software). Place and Duration of Study: Department of Chemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…(2016) of 9.3%–10.4% and Gbaa et al . (2019) of 10.70%–12.35% in a related study on traditional breakfast cereal. The low moisture content in the study indicated a good keeping quality of the cereal‐based breakfast products.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…(2016) of 9.3%–10.4% and Gbaa et al . (2019) of 10.70%–12.35% in a related study on traditional breakfast cereal. The low moisture content in the study indicated a good keeping quality of the cereal‐based breakfast products.…”
Section: Resultsmentioning
confidence: 93%
“…Similar studies by Gbaa et al . (2019) on sorghum‐based mumu fortified with watermelon rind had vitamin C ranging from 5.97 mg/100 g to 8.12 mg/100 g. Oyster mushroom supplementation which is the source of vitamin C in the cereal‐based breakfast product can only be limited at 10% and further addition lead to decrease in vitamin C content. Vitamin C (ascorbic acid) serves as a coenzyme for iron absorption and is beneficial to wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Watermelon is also high in citrulline, an amino acid the body make use of to make another amino acid, arginine (used in the urea cycle to remove ammonia Cal from the body) [7]. The research by Gbaa et al, [8] has shown that blending sorghum/groundnut mumu with watermelon rind powder had significantly improve the nutritional value of the product in terms of its macro and micronutrients content thereby improving the nutritional status of the consumers.…”
Section: Introductionmentioning
confidence: 99%